ADAPTIVE REACTIONS OF LUNGS AT INFLUENCE OF VARIOUS DOSE OF THE CIGARETTE SMOKE (Experimental biology, 2016)
Data on Protective and adaptive reactions of aeriferous and respiratory parts of lungs on the influence of various doses of cigarette smoke are provided. Adaptation and reactive changes of organellas, permeability disorders of the epithelial cells are shown. Electronically – microscopic research of respiratory department of lungs at influence of small doses of a cigarette smoke revealed sharp increase in volume of a kernel and kernel in the alveolotsitakh of the 1st type. The plasmatic membrane of an apikalny surface of alveolotsit of the 1st type formed long cytoplasmatic shoots and invagination. In a tsitolpazma of alveolotsit of II type the sizes the osmiofilnykh of little bodies due to prevalence of electronic and transparent material sharply increased. There were huge lamellar little bodies which are squeezing and pushing aside a kernel to the periphery of a cage. Big dose of cigarette smoke led to the expressed destructive changes of ciliate and caliciform cells of cylindrical epithelium of tracheas of experimental animals.
Keywords: Respiratory division; goblet cells; macrophages; the air-blood barer and cigarette smoke.